Depression and Anxiety in Patients with Corona Virus Disease 2019 - Trixie Almira (Global Health Science Group, 2020)
The novel corona virus disease pandemic was first reported in December, 2019 in Wuhan, China. An infectious disease pandemic such as COVID-19 is linked to psychological distress and symptoms of mental illness such as depression and anxiety. The purpose of this literature review aims to discuss mental health problems in the form of depression and anxiety related to the COVID-19 pandemic. The research method used is literature review by collecting 28 articles taken from 2016-2020, the journals were collected from various sources, namely Pubmed, Medscape, Google scholar and WHO. Result of journals called later in the analysis using the Systematic Literature Review method is by collecting, evaluating, and developing research on a particular focus topic The results obtained were that people with COVID-19 had higher levels of depression and anxiety. Factors that increase the risk of depression and anxiety are old age, lack of physical activity, health literacy, education, low social status, and not consuming healthy foods. It is also caused by the body's immune response to the virus by psychological stress.